A gamified augmented reality application for human-machine interaction in CNC milling machine - Abd Rani, Nadia Hanim (2022)
The 4th industrial revolution and the digital transformation are prevailing factors in the manufacturing industry and augmented reality (AR) currently plays an important role to undertake the challenges in integrating technologies to expedite the march towards the revolution. The manufacturing evolution provided more efficient techniques to extend the humans capabilities and cost reduction in various areas. Computer Numerical Control (CNC) milling machine was the most difficult machine as it takes several procedures with different processes. It requires skilled users and knowledge in programming, 3-D model design, and understanding machine language. Therefore, machining competencies in CNC machines practices are highly demanded. Tool length offsets are one of the most widely misunderstood aspects of CNC milling operation and these procedures rely on human-input parameters. Human-machine interaction (HMI) is an interaction and communication between human and a machine, a dynamic technical system and it is the methodology for evaluation of user interface techniques. The objectives of this research are to measure the ability of beginners, and empowering the CNC milling machine operation. A gamified AR application is to be developed, called CNC Milling Interaction Learning (CMiL), to assist user understanding in performing the machining task. Then, the AR application effectiveness is being evaluated for user acceptance of this technology. This research also developed a conceptual framework on HMI with cybergogy learning concept for human engagement and heutagogy learning. The items difficulties in handling CNC milling machine were identified through and experiment which involved 31 participants. Numbers of softwares have been used for the AR application development. The hardware used was Boxford VMCi300 CNC milling machine and, tablet or mobile as the device to run the CMiL application. CMiL effectiveness evaluation, involved 20 CNC milling machine users and experts. A conceptual framework was developed and validated by the CNC milling machine expertise and curriculum developer. As a result, 14 items were identified as difficulties to empower CNC milling machines for beginners. An immersive 3D gamified AR application was developed to enhance the user experiece and user interface for better understanding with video, images, tasks, simulation in the AR environment. The CMiL application contents was 100% function, pertinent with the real-scene machine procedures, validated by CNC machines experts. Therefore, 90.5% of CMiL users have accepted that CMiL can be act as the learning platform for the CNC Milling machine, 76.1% agreed that the apps enhanced their knowledge and 85.7% agreed that the CMiL apps enhanced their skills. The newly developed conceptual framework on humanistic theory guided by technology-based learning design shows the relationships and connectivity of the gamified AR application. 90% experts concurred that the conceptual framework of cybergogy and heutagogy learning concept by CMiL application leads to assist user interface and user experience of the HMI elements. This can be concluded that using AR via gamification and digital content offers a rich experience, assist and support the enhancement of psychomotor phase in human skills development. It is a tool for learning motivation and enhances cognitive, persistence, and competencies in human performance.